Clinical Utility of the Trajectory of Serum Bilirubin and International Normalized Ratio Values in Hepatitis B Virus-Related Acute-on-Chronic Liver Failure - Song YQ; Fu XY; Yan SY; Qi RB; Zhou YJ; Liang JW; Zhang JQ; Ye LP; Mao XL; Li SW (International Journal of General Medicine)
Ya-qi Song,1,2,* Xin-yu Fu,1,3,* Si-yan Yan,4 Rong-bin Qi,5 Yi-jing Zhou,1 Jia-wei Liang,6 Jin-qiu Zhang,1 Li-ping Ye,1 Xin-li Mao,1 Shao-wei Li1 1Department of Gastroenterology, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, Zhejiang, People’s Republic of China; 2Department of Gastroenterology, Taizhou Hospital of Zhejiang Province, Linhai, Zhejiang, People’s Republic of China; 3Dalian Medical University, Dalian, People’s Republic of China; 4Department of Gastroenterology, Taizhou Hospital of Zhejiang Province, Zhejiang University, Linhai, Zhejiang, People’s Republic of China; 5Department of Respiratory Medicine, TaiZhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, Zhejiang, People’s Republic of China; 6Department of Thoracic Surgery, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin-li Mao; Shao-wei Li, Department of Gastroenterology, Taizhou Hospital of Zhejiang Province affiliated With Wenzhou Medical University, Linhai, Zhejiang Province, People’s Republic of China, Email maoxl@enzemed.com; li_shaowei81@hotmail.comBackground and Aim: Acute-on-chronic liver failure (ACLF) is a rapidly progressive and highly fatal condition. Early identification of critically ill patients is crucial. Hepatitis B virus-related ACLF (HBV-ACLF), the main cause of ACLF in China, is characterized by liver failure and coagulation dysfunction. Dynamic changes in total bilirubin (TB) and international normalized ratio (INR) can reflect disease progression. This study aims to investigate the clinical application of dynamic trajectories of TB and INR in HBV-ACLF patients.Methods: Retrospective data from 194 patients at Taizhou Hospital, China (Jan 2012 - June 2023), meeting COSSH-ACLF criteria, were analyzed. A latent class mixed model (LCMM) identified three trajectory groups (declining, stable, fluctuating) based on bilirubin and INR changes. Clinical applicability of these groups was investigated.Results: The 194 patients were divided into the trajectory groups mentioned above. The declining group had lower predicted scores and a better prognosis. The stable and fluctuating groups had worse prognosis compared to the declining group (P< 0.001). Artificial liver support did not improve short-term prognosis for the stable group; instead, it was a risk factor (OR 2.16, 95% CI [0.23– 3.79], P=0.007). Subgroup analysis showed no interaction between predictive models and trajectory groups. Additionally, trajectory grouping improved the predictive effectiveness of existing models.Conclusion: Based on our trajectory analysis, patients with a continuous declining in bilirubin and INR values showed the best prognosis, highlighting the clinical significance of trajectory grouping in treatment decisions. Trajectory grouping can complement existing scoring models, improving predictive effectiveness.Keywords: dynamic trajectories, short-term prognosis, artificial liver support, acute-on-chronic liver failure